Is there financial acceleration in african banking? Studies on 25 african countries - Sumantika, Ahsan (Proceeding International Conference on Accounting and Finance, 2024)
African countries are one of the regions consisting of many developing countries. The behavior of price-cost margins carried out by banks is an issue that needs to be looked at further because it can damage economic development. The main objective of this study was to investigate whether there was a financial accelerators behavior carried out by banks in African countries. Author found evidence of financial accelerators behavior carried out by African banks. Using a sample of 153 banks with 1415 observational data from 2005 to 2021, the author found that loan was negatively related to the amount of price-cost margin received by the bank. Furthermore, when there is a recession marked by worsening economic growth, the reduction in loans actually increases bank profits which are characterized by higher price-cost margins. Researchers also found that the worse the recession, the higher the price-cost margin that banks receive